Randomized trial of Roux-en-Y gastric bypass versus sleeve gastrectomy in achieving excess weight loss. Issue 3 (30th November 2016) - Ignat, M; Vix, M; Imad, I; D'Urso, A; Perretta, S; Marescaux, J; Mutter, D
Abstract: Background: Robust data on quality of life (QoL) after different techniques of bariatric surgery are sparse. This RCT compared excess weight loss (EWL) and QoL after sleeve gastrectomy versus Roux-en-Y gastric bypass (RYGB). Methods: Obese patients were assigned randomly to RYGB or sleeve gastrectomy. The primary outcome measure was EWL. Secondary outcomes included QoL, co-morbidity, adverse events, vitamin and glycolipid status. QoL was assessed before and annually after surgery, using the Moorehead–Ardelt Quality of Life Questionnaire II (M-A-QoLQII) and Gastrointestinal Quality of Life Index (GIQLI). Results: One hundred patients were enrolled, 45 in the RYGB group and 55 in the sleeve gastrectomy group. Mean postoperative EWL at 1, 2, 3 and 5 years was 80·4, 79·8, 83·0 and 74·8 per cent respectively after RYGB, and 83·0, 77·8, 66·3 and 65·1 per cent after sleeve gastrectomy ( P = 0·017). Mean M-A-QoLQII score before surgery and at 1, 2, 3 and 5 years after operation was 0·5, 1·6, 1·7, 2·1 and 1·4 respectively after RYGB, and 0·3, 1·7, 1·5, 1·5 and 1·2 after sleeve gastrectomy. Mean GIQLI score before and at 1, 2, 3, 5 years after RYGB was 96·4, 113·8, 113·3, 113·4, 111·7, compared with 90·7, 113·9, 114·5, 113·1 and 113·0 for sleeve gastrectomy. The improvement was significant compared with preoperative values ( P < 0·001 for M-A-QoLQII and GIQLI), with no difference between groups ( P = 0·418 and P = 0·323 respectively). RYGB resulted in higher readmission rates ( P = 0·002) and length of hospital stay ( P = 0·006) than sleeve gastrectomy. Conclusion: RYGB and sleeve gastrectomy resulted in equivalent, long-standing QoL improvement. RYGB resulted in more stable weight loss but was associated with higher readmission rates. Registration number: NCT02475590. Abstract : Bypass better in the long term